1967
DOI: 10.1063/1.1754819
|View full text |Cite
|
Sign up to set email alerts
|

INTERACTION OF CONDUCTION AND INDUCED CURRENTS IN Nb3Zr WIRES SUBJECTED TO AXIAL FIELDS

Abstract: A residual magnetization induced in Nb3Zr wires by axial fields appreciably enhances Ic. Further, the presence of a conduction current as an axial field Hz is removed not only leads to considerably increased residual moments but also enables the wire to support currents at H = 0 much larger than is possible in the virgin state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1970
1970
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Such a configuration has been studied in [7,14]. Experiments have shown that the magnetic field can increase the critical current down the wire [15].…”
Section: Example 1: Wire With Longitudinal Fieldmentioning
confidence: 99%
“…Such a configuration has been studied in [7,14]. Experiments have shown that the magnetic field can increase the critical current down the wire [15].…”
Section: Example 1: Wire With Longitudinal Fieldmentioning
confidence: 99%